Comparison of Judaism and Christianity : A Contemporary Reappraisal - Dr. Chistyakova-Luce1,; Dr. Chistyakov- Clem, (Al-Qanṭara, 2023)
The creation of the universe still remains a mystery to many of us. Almost all mankind is obsessed with trying to discover how the creation of everything that exists came about. Some are convinced about the divine existence of God while others are atheist. The religious people are also faced with many differences and disagreement about the existence and the nature of the real God. The purpose of this paper is to compare and contrast two specific characteristics that are evident in Christianity and Judaism. To understand the differences in both religions, we need to understand the differences in notions of these religions. The notion of afterlife is common for both these religions. While Judaism believes in afterlife, Christianity explains this notion a little bit different. Christian people believe in resurrection. These understandings are similar, but not the same. Judaism afterlife is believed, but not explained. Jewish people do not try to explain what they cannot understand; they just believe in it. Christian religion believes in the day when resurrection comes and religious people will live forever in the Garden of Eden. Keywords- Comparison of Judaism and Christianity